2012
DOI: 10.1007/s00122-012-1860-4
|View full text |Cite
|
Sign up to set email alerts
|

Simple sequence repeat marker development from bacterial artificial chromosome end sequences and expressed sequence tags of flax (Linum usitatissimum L.)

Abstract: Flax is an important oilseed crop in North America and is mostly grown as a fibre crop in Europe. As a self-pollinated diploid with a small estimated genome size of ~370 Mb, flax is well suited for fast progress in genomics. In the last few years, important genetic resources have been developed for this crop. Here, we describe the assessment and comparative analyses of 1,506 putative simple sequence repeats (SSRs) of which, 1,164 were derived from BAC-end sequences (BESs) and 342 from expressed sequence tags (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 65 publications
2
46
1
Order By: Relevance
“…In the present investigation, we applied 50 widely distributed SSRs to evaluate the genetic diversity and identify diverseaccessions/groupofaccessionsamongalargesetof168 accessionsoflinseed.Atotalof337allelesweredetectedfrom50 SSRswithanaverageof6.74allelesperSSRs.Thisaverageallele numberwasfoundtobehigherthanthatreportedearlier (RooseAmsalegetal.2006;Dengetal.2011;Palietal.2014;Soto-Cerda etal.2012Cloutieretal.2012b).Thehigherallelenumber mightbeduetothelargeanddiversesetofaccessionsandwidely distributed SSRs used in the present study. The three markers namelyLU_2332,LUSc_38_01andLuSc_196_02having13, 12 and 12 alleles with PIC value above 0.80 seems to be highly informativeandcouldbefurtherutilizedinevaluatingothersets oflinseedgermplasm.TheaveragePICvalue(0.47)wasfoundto be higher than those reported by Soto-Cerda et al (2011, Cloutier et al (2009Cloutier et al ( , 2012b. While Deng et al (2010) reported slightly higher average PIC value (0.56) than found in the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…In the present investigation, we applied 50 widely distributed SSRs to evaluate the genetic diversity and identify diverseaccessions/groupofaccessionsamongalargesetof168 accessionsoflinseed.Atotalof337allelesweredetectedfrom50 SSRswithanaverageof6.74allelesperSSRs.Thisaverageallele numberwasfoundtobehigherthanthatreportedearlier (RooseAmsalegetal.2006;Dengetal.2011;Palietal.2014;Soto-Cerda etal.2012Cloutieretal.2012b).Thehigherallelenumber mightbeduetothelargeanddiversesetofaccessionsandwidely distributed SSRs used in the present study. The three markers namelyLU_2332,LUSc_38_01andLuSc_196_02having13, 12 and 12 alleles with PIC value above 0.80 seems to be highly informativeandcouldbefurtherutilizedinevaluatingothersets oflinseedgermplasm.TheaveragePICvalue(0.47)wasfoundto be higher than those reported by Soto-Cerda et al (2011, Cloutier et al (2009Cloutier et al ( , 2012b. While Deng et al (2010) reported slightly higher average PIC value (0.56) than found in the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…In flax, large numbers of genomic SSR markers have already been developed (Cloutier et al, 2009, 2012a; Deng et al, 2010; Sandip et al, 2012). Three microsatellite isolation methods, all utilizing next-generation sequencing methodologies, have rapidly pinpointed SSR markers for evaluation of diverse oilseed flax genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Such rapid advances demonstrate the value of this sequencing technology for SSR marker discovery (Sandip et al, 2012) and recent characterization among almost all fiber and oilseed flax cultivars (Roose-Amsaleg et al, 2006; Deng et al, 2010). Notably, 1506 putative simple sequence repeats have recently been assessed using a panel of 16 flax accessions, resulting in discovery of 818 novel polymorphic SSR primer pairs (Cloutier et al, 2012a). However, specific progress using these SSR makers toward the development of flax breeding programs must first await development of other necessary genetic and genomic resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Codominant markers usually have a PIC value from 0.5 to 1 [54]. It implies that selected SSR loci were highly informative.…”
Section: Correlation Analysismentioning
confidence: 99%